An Assessment of Inclusion in the Governance of Bangladesh’s Agri-Food System to Face Climate Crisis - Irfanullah, Haseeb (International Water Management Institute, 2023)
This exploratory study relied on secondary data review relating to inclusive governance in agri-food systems, as well as an analysis of Bangladesh’s contemporary agriculture, food systems, climate change, conservation, and natural resource management policies and interventions. Based on the literature review, key practices/initiatives were mapped against an analytical framework consisting of seven dimensions of inclusive governance, namely representation, participation, capacity and skills, accessibility, financial resources, knowledge system, and innovation. This review also helped to identify governance challenges and gaps based on four dimensions of food systems: environment, economy, society and culture, and policy and governance, which were mapped against seven dimensions of inclusive governance. Finally, to identify the opportunities to address the governance challenges in a more socially inclusive and gender equitable way, this research focused on several issues which will contribute to transforming the agri-food system of Bangladesh making it more resilient under changing climate.